DEVELOPMENT OF ANGLO-SAXON TRADITIONS IN THE SYSTEMS OF EDUCATION IN THE USA AND RUSSIA: THE RELEVANCE OF THE RESEARCH - Loginova , Marina (Bulletin of Psychology and Pedagogy of Altai State University, 2021)
Starting in the 90s, Russia tries to become a part of the global system of education, where the USA’s leadership is absolute. This tendency leads to the adoption of the traditions that are characteristics of the Anglo-Saxon educational system. Such like adoptions become a source of controversy over the traditions historically typical for the Russian pedagogical culture. The article deals with the importance of Anglo-Saxon traditions adoption study in the Russian educational system.